L’accueil des laïcs dans les monastères (ve-ixe siècle), d’après les règles monastiques - Michèle Gaillard (Bulletin du Centre d’Études Médiévales d’Auxerre)
Through the monastic rules, written between the fifth and the ninth century, we perceive little concrete data about specific buildings reserved for the reception of laymen in the monasteries; two topographic data are intangible: on the one hand, we have an hotel reserved for people from outside the community and on the other hand we find a strictly limited space for the monastic community. But there was no necessity of an absolute separation between monks and hosts. The rules are more explicit and sometimes divergent concerning the general conditions how to receive laymen and how to organize an exchange between laymen and monks; they clearly distinguish visitors and postulants, and they often entrust the control of the two categories to the Ancients.